3-D EARTH MODELS REGIONAL AND DETAILED EXPLOSION AND EARTHQUAKE SEISMOLOGICAL STUDIES - Popova O.G.; Popov M.G. (My University, 1997)
3-D models are offered for velocity distribution and crustal and upper mantle structure in areas of large earthquakese (Shemakha, Spitak, and Groznyi) and mineral deposits (Muruntau deep borehole area). The models were derived using data of deep seismic sounding recording of converted earthquake waves. The comparative efficiency of the recording arrangements used is evaluated for all of the areas. Some generalizations are made relating to the structure of the source zones. Optimal observation arrangements are suggested for the combined use of converted earthquake waves and deep seismic sounding and for the recording of converted earthquake waves alone for locating crust - upper mantle interfaces and velocity anomalies.